SOME ASPECTS OF IMPROVING THE REGULATION OF FOREIGN TRADE ACTIVITIES OF BUSINESS ENTITIES - Turayev N. M. (American Journals, 2024)
The analysis of external and internal factors in the development of foreign trade activities of business entities showed unique results. In the organization and internal organization of foreign trade activities of business entities, collecting data and re-examining them creates a factor such as the attitude of an entrepreneur. Most of the problems are related to the legal and economic literacy of the entrepreneur, and it shows his attitude to social processes.
Keywords: Business entities, foreign trade activities, export-import of goods and services, foreign trade contracts, transport contracts, customs warehouses, road tracking documents, certificates, innovative and digital technologies, time factor, management.